SOCIAL-ECONOMIC SECURITY OF THE CITY (Economic journal of Lesya Ukrainka Volyn National University, 2019)
Introduction. Globalization of the world caused to increasing role of cities. That is why a city as the most important  element of spatial social-economic system of the society is the object in many researches for a long time. One of the advisable directions of researches concerning cities as the element of spatial social-economic system of the society is research of city in economic security studies – as the object of social-economic security. Such direction is grounded in the context of increasing the responsibility of State for creating stable conditions for citizens’ life and business activity on some territories. The purpose of the article. Researches that are directed on the essence and features of social economical security of the city should begin from the point of identifying the content of notion “social economical security of the city”. Attempts of explaining such notion without building necessary subject field can be considered as the common imperfection of modern studies of city social economical security. Absence of necessary subject field deprives many definitions of required validity and arguments.Results. Necessary subject field is formed to define essence and features of social-economical security of the city as an urbanistic geosystem (urbageosystem). Elements of such subject field are components of “risk society” concept, imperatives of protective and integrative approaches that are widely spread in economic security studies, dual character of notion “social-economical security of the city” and content on notion “city” that is defined by the author. There is content of notion “social-economical security of the city” elucidated using elements of built subject field.High level of the social-economical security of the city designates its secure conditions – there are no significant and intensive changes with a negative character in condition of urbageosystem in a current time and a nearest future. In the general case such changes with a negative character can emerge because of threats to urbageosystem. There are some complex characteristics used to describe secure condition of the city. Such characteristics should meet some requirements (convenience of living in the city, dynamic of development of the city, quality of life in the city, transparency of public administration in the city, conditions of social-economic institutes that provide needs on inhabitants of the city).Every of complex characteristics of the city secure condition contains some subcharacteristics. Suggested complex characteristics and subcharacteristics of the city secure condition are not only closely related, but some of them are contradictory.Conclusions. Complex characteristics and subcharacteristics of the city security state need future more detailed research as well as  indicators for their quantitative description.
Keywords: city, social-economic security, subject field, security state of the city, characteristics